Estimation of leisure time physical activity and sedentary behaviour among school adolescents in Nepal - Paudel, Susan (BioMed Central, 2014)
BACKGROUND: Leisure-time physical activity is essential for healthy and physically active life; however, this domain of physical activity is less common in developing countries. Information on leisure time physical activity and sedentary behaviour among Nepalese population is not available. The study was carried out to assess leisure time physical activity and sedentary behaviour among high school adolescents and identify the associated factors in Nepal. METHODS: A cross-sectional descriptive study was carried out in Banke district, Nepal in 2013 among higher secondary school students using self-administered questionnaire based on International Physical Activity Questionnaire. A sample of 405 students, 178 females and 227 males, of the age–group 15 to 20 years from seven schools were included in the study. Multivariate logistic regression analysis was carried out to identify factors associated with participation in leisure time physical activity and sedentary behaviour. RESULTS: Engagement of female in leisure time physical activity was lower but mean time spent on sitting per day was higher. Students who walked to school and have playground/parks near home, younger females (OR = 3.09, 95% CI: 1.18-8.08), females living in nuclear families (OR: 2.16, 95% CI: 1.01-4.62) and males who cycled to school (OR: 8.09, 95% CI: 2.35-27.80) and have provision of extra-curricular activities (OR: 2.49, 95% CI: 1.04-5.97) were more likely to be engaged in leisure time physical activity. On the other hand, students who did not have playground in school and lived in rural areas were more likely to sit for more than 6 hours a day. Likewise, male students of private school (OR: 6.41, 95% CI: 2.89-14.21), who used vehicle to reach school (OR: 5.90, 95% CI: 1.26-27.75) and have no provision of extra-curricular activities (OR: 2.98, 95% CI: 1.09-8.07) had longer sitting time. CONCLUSION: Difference in leisure time physical activity and sedentary behaviour was found among male and female school adolescents. Interventions are needed not only to promote leisure time physical activity but also to reduce sedentary behaviour among this group.